A protocol for a prospective, multicentre observational study to determine if nonanaemic iron deficiency worsens postoperative outcome in patients undergoing elective surgery for resection of colorectal cancer: The NATO study. (29th October 2022) - Miles, Lachlan F.; Pac Soo, Vanessa; Braat, Sabine; Burgess, Adele; Heritier, Stephane; Smart, Philip; Tan, Nicole; Parker, Anna; Burbury, Kate L.; Story, David A.; ,
Abstract: Background: Preoperative absolute and functional iron deficiency anaemia is associated with poor postoperative outcomes in patients undergoing surgery for colorectal cancer. It is biologically plausible that "early", or "nonanaemic" iron deficiency may also be associated with worse postoperative outcomes in similar cohorts, albeit at lesser severity than that seen for anaemia. The evidence supporting this assertion is of low quality. Methods: We have designed a prospective, observational study to delineate associations between preoperative non‐anaemic iron deficiency and postoperative outcomes after surgery for colorectal cancer. Patients without anaemia, undergoing elective surgery for colorectal cancer will be allocated to an iron replete or an iron deficient group based on preoperative transferrin saturation. The primary outcome is days alive and at home on postoperative day 90. Secondary outcomes include days alive and at home on postoperative day 30, length of hospital stay, readmission to acute care, postoperative complications, health‐related quality of life scores, quality of postoperative recovery, and requirement for allogeneic blood transfusion. The planned sample size is 422 patients, which has 80% power to detect a two‐day difference in the primary outcome. The study commenced in May 2019. Conclusion: The results of this study will provide patients and clinicians with high‐quality evidence concerning associations between nonanaemic iron deficiency and patient‐centred outcomes after surgery for colorectal cancer. The study will be conducted in multiple urban and rural centres across Australia and New Zealand. The results will be highly generalisable to contemporary surgical practice and should be rapidly translated.